Pengaruh Teknologi Text-to-Speech Berbasis Deep Learning Terhadap Pemahaman Bunyi dan Intonasi dalam Pembacaan Puisi Pada Siswa Kelas XI SMA Negeri 7 Medan Tahun Ajaran 2025/2026 - Crisdayanti Sitorus; Beslina Afriani Siagian; Harlen Simanjuntak (PGSD Universitas Muria Kudus, 2026)
This study aims to determine the effect of using Deep Learning-based Text-to- Speech technology on students’ understanding of sound and intonation in poetry reading among Grade XI students at SMA Negeri 7 Medan in the Academic Year 2025/2026. This research employed a quantitative method with a one-group Pretest-Posttest design. The sample consisted of Grade XI students of SMA Negeri 7 Medan who were given tests before and after the implementation of Deep Learning-based Text-to-Speech technology. The instrument used was a poetry reading performance test assessed based on indicators of sound and intonation comprehension. The data were analyzed using a t-test to determine the difference between the results before and after the treatment. The findings showed that the average score of students’ understanding of sound and intonation before using Deep Learning-based Text-to-Speech technology was categorized as fair, while after using the technology, the average score increased and was categorized as good. The t-test results indicated that the significance value (Sig. 2-tailed) was < 0.05, which means that there was a significant effect between the Pretest and Posttest results after the use of Deep Learning-based Text-to-Speech technology. Thus, it can be concluded that the use of Deep Learning-based Text-to-Speech technology has a significant effect on improving students’ understanding of sound and intonation in poetry reading among Grade XI students at SMA Negeri 7 Medan.